Pengaruh Tingkat Pendidikan , Upah Dan Umur Terhadap Produktivitas Tenaga Kerja (Studi Kasus Pada Rumah Makan Padang Saiyo Sakato) - Muhamad Haqqi Zamani; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractProductivity is a description of the ability of workers to produce output. The higher the output produced by a worker, the higher the level of productivity of the worker. Saiyo Sakato Restaurant is one of the largest restaurants in Malang City with a system of ownership and family relations that have been passed down from generation to generation. However, there are many factors that will affect the productivity of the workforce at the Saiyo Sakato restaurant. Therefore, what will be analyzed in this study is the effect of education level, wages and age on labor productivity (a case study on the Padang Saiyo Sakato restaurant).This study aims to analyze the effect of education, wages, and age on labor productivity (a case study on the Padang Saiyo Sakato restaurant). In this study, primary data was used by distributing questionnaires to 63 employees of RM. Saiyo sakato, with a list of prepared questions. To achieve the goal, in this study using multiple linear regression analysis method.The results of this study indicate that the variables of wages and age have a positive and significant effect on the productivity of RM. Saiyo sakato. While the education variable has no significant effect on the productivity of RM.Saiyo sakato. Keywords: Productivity, Education Level, Wages, and Age